HOW TO TEACH CHILDREN TO WRITE IN RUSSIAN CORRECTLY IF RUSSIAN IS NOT THEIR NATIVE LANGUAGE Version for Native Karakalpak Language Speakers Part 2 - Ostapenko, Andrey Alexandrovich (SCIENCE and SOCIETY, 2026)
The article discusses a methodology for developing literate writing skills in Russian among primary school children who are non-native speakers, particularly for the Karakalpak audience. The author distinguishes two components of writing skills – content-related and technical – and details the sequence of their formation. A model for the gradual development of speech abilities, from understanding spoken language to cursive writing, is proposed. Special attention is paid to factors influencing the acquisition of Russian as a non-native language: degree of language similarity, type of writing system, and presence of a bilingual environment. Based on the analysis of these factors, an adaptive teaching strategy is built, considering the specifics of the students’ native language.